Porous Carbons Derived from Desilication Treatment and Mixed Alkali Activation of Rice Husk Char for Supercapacitors. Issue 3 (1st February 2021) - Zhang, Shuping; Zhang, Qiong; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi
ABSTRACT: Porous carbons with micro-meso hierarchical porous structure derived from rice husk char were first prepared by desilication treatment and mixed alkali activation. The as-obtained porous carbons (Na-K/rRHC800) exhibited a well-developed hierarchical porous carbon with a high specific surface area of 3046 m 2 g −1 and numerous interconnected pores with a large pore volume up to 1.70 cm 3 g −1 composed of micro-, meso-, and macropores, as well as high graphitization degree. In addition, the Na-K/rRHC800 electrode displayed a high specific capacitance of 312.0 F g −1 at the current density of 0.2 A g −1, an excellent cycling stability (retention of 92.6% after 10, 000 cycles) and energy density of 10.8 Wh kg −1 in 6 M KOH. The results indicated that the facile preparation route shows great ease in controlling the pore structure of porous carbons derived from a green and sustainable feedstock of rice husk char for supercapacitor application. Furthermore, the results also improved the perspectives for the economy of the full-scale valorization of rice husk by fast pyrolysis.